Female Palm Oil Plantation Workers PT Bakrie Pasaman Plantation Koto Balingka District, West Pasaman Regency 1998-2020 - Putri, Fauziah Delsa; Midawati, Midawati; Gulo, Anatona (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This study aims to see how the lives of female workers who work at PT. Bakrie Pasaman Plantation, Koto Balingka District, West Pasaman Regency in 1998-2020. The method used in this study is the historical method through four stages, namely, heuristics, source criticism, interpretation and historiography. The results of this study indicate that the large-scale acceptance of women on the plantation of PT. Bakrie Pasaman Plantation in 1998 was due to the expansion of plantation land and the need for additional workers. women who work at PT. Bakrie Pasaman Plantation generally have low education, because they do not need higher education to work as laborers on oil palm plantations. The factors that encourage them to work as laborers are to meet the family's economy, have low education and feel bored. As laborers, women are able to improve the family's economy, improve their children's education and facilities (vehicles, communication tools and household furniture).